Andhap Asor, Pracaya, lan Mituhu Moralitas Pemikiran Pendidikan Moralitas Pemikiran Pendidikan Moralitas Pemikiran Pendidikan Moralitas Pemikiran Pendidikan K.H. Hasyim Asy’ari - mawardi, kholid (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2007)
K.H. Hasyim Asy’ari is one Islamic scholar that has global insight without ripped out from tradition that grows him up (Javanese). He develops Islamic ideas about education with local sense. His thought structure about education philosophically based on view that every activity conducted to seek Allah’s acceptance and place good characters as basic morality. From that two basic values bring about adab (moral) as its operational.